Modified vac dressing in sternal wound infection management. Cheap and feasible technique in developing country - Sembiring, Yan Efrata (Folia Medica Indonesiana, 2017)
Sternal wound infection is a rare but serious complication of cardiac surgery leading to prolonged hospital stay and higher mortality. In the last decades several treatment modalities have been described, of which vacuum-assisted closure (VAC) shows the most promising results. However, the VAC therapy system is expensive, requires extensive amounts of product and needs a power source at all times. Modified VAC dressing to treat sternal wound infection is cheap and feasible technique to use in develop country. This technique can be use as an alternative to the original vacuum-assisted closure and hadshown to serve its function in providing adequatevacuum pressure for wounds.